Evaluating social and behavioural impacts of English smoke-free legislation in different ethnic and age groups: implications for reducing smoking-related health inequalities. Issue 5 (2nd August 2010) - Lock, K; Adams, E; Pilkington, P; Duckett, K; Gilmore, A; Marston, C
Abstract : Objective: To explore social and behavioural impacts of English smoke-free legislation (SFL) in different ethnic groups. Design: A longitudinal, qualitative panel study of smokers using in-depth interviews conducted before and after introduction of SFL. Participants: A purposive sample of 32 smokers selected from three ethnic groups in deprived London neighbourhoods with approximately equal numbers of younger and older, male and female respondents. Results: SFL has had positive impacts with half smoking less and three quitting. Although there were no apparent differences in smoking and quitting behaviours between groups, there were notable differences in the social impacts of SFL. The greatest negative impacts were in smokers over 60 years, potentially increasing their social isolation, and on young Somali women whose smoking was driven more underground. In contrast, most other young adult smokers felt relatively unaffected by SFL, describing unexpected social benefits. Although there was high compliance, reports of illegal smoking were more frequent among young, ethnic minority smokers, with descriptions of venues involved suggesting they are ethnically distinct and well hidden. Half of respondents reported stopping smoking in their own homes after SFL, but almost all were Somali or Turkish. White respondents tended to report increases in home smoking. Discussion: Although our study suggests that SFL can lead to reductions in tobacco consumption, it also shows that impacts vary by ethnicity, age and sex. This study highlights the importance of understanding the meaning of smoking in different social contexts so future tobacco control interventions can be developed to reduce health and social inequalities.